Impacted Inverted Supernumerary Tooth with Regional Odontodysplasia : A Rare Case Report - Ashna​ Biju; A P Kavitha; . Krupashankar; D B Megha (Journal of Multidisciplinary Dental Research)
Regional Odontodysplasia (RO) is a rare developmental disturbance of the teeth affecting the structure of the teeth. The etiology of RO is largely unknown however it is known to consist both the mesodermal and the ectodermal components. The occurrence of RO is twice common in the maxilla than in the mandible. RO most often is known to involve the maxillary central and lateral incisors. The prevalence of RO is rare thus available literature regarding the site and gender predilection, clinical manifestations and radiographic features is limited. Therefore, this case report is presented to provides an overview of the radiographic features of RO Keywords: Ghost teeth, CBCT, Regional odontodysplasia